Inventory and Identification of Rosaceae Family in the Surroundings of Farm House Lembang - Vania Ulfa Ramdhanawati; Wirdah Triana Octaviani; Ateng Supriyatna (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Rosaceae is a rose family that belongs to a large plant family. This family consists of 3,000-4,000 species distributed among 100-120 genera. Rosaceae exhibits distinctive characteristics found in its flowers. Generally, the Rosaceae family possesses perfect flowers. Therefore, the purpose of this research is to identify the plant species that belong to this family and understand their characteristics. The research methodology encompasses three stages: sample collection, direct observation, and documentation of gathered data. The findings reveal five plant species divided into two genera, namely Rosa and Fragaria. These species include Rosa alba, Rosa chinensis, Rosa damascena mill, Rosa hybrid tea, and Fragaria ananassa. Thus, the conducted research provides insights into the characteristics of the Rosaceae family. Judul bahasa Indonesia: Inventarisasi dan Identifikasi Famili Rosaceae di Sekitar Kawasan Farm House Lembang